Revitalizing Cultural Heritage: An AR-Based Digital-Preneurship Start-Up for Sustainable Tourism and Community Empowerment - Som, Rit; Kiat, Ton; Rossi, Giovanni (Journal of Social Entrepreneurship and Creative Technology, 2025)
Cultural heritage is a vital aspect of community identity and history, yet many regions face challenges in preserving and promoting their heritage in the face of modern economic pressures. Traditional tourism practices often lead to the commercialization and degradation of cultural sites, while communities struggle to benefit economically from their heritage. Augmented Reality (AR) technology offers a promising solution by providing immersive, interactive experiences that can both preserve and promote cultural heritage while supporting sustainable tourism. This study explores the implementation of an AR-based digital-preneurship start-up model designed to revitalize cultural heritage through tourism while empowering local communities. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with both local stakeholders and tourists. The findings reveal that the AR platform significantly enhanced both tourist engagement and local economic outcomes, increasing community participation in tourism-related activities and boosting income for local businesses. The study concludes that AR-based digital-preneurship offers a scalable, sustainable model for cultural heritage revitalization, providing communities with a new avenue for economic development and cultural preservation. This research contributes to the growing body of knowledge on the intersection of technology, entrepreneurship, and sustainable tourism.